KREASI BAHAN SISA MAKANAN DI KITCHEN HOTEL FAVE PEKANBARU - Sarlianto, Setyo Tri; Sidiq, Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Residual of food material can be defined as the percentage of remaining unutilizedmaterial in food processing which could be assumed as food waste that could beset as a perimeter for effectiveness of a menu.This research is aimed to determinekind of innovations which could be performed by kitchen line management of FaveHotel,Pekan Baru regarding food residual handling management. The topic to bediscussed in this research covering residual food planning management, processesof creativity and the end products of innovations. The research took place at FaveHotel Pekan Baru on March till April 2018. This research use descriptivemethodology with qualitative approach. All data is collected through observations,interviews and documentations. Through this research, the writer draw aconclusion that residual food, instead of to be disposed, could be reutiliized by theway of creating it to become e new useful products and would play an effective rolein food cost management of Fave Hotel, Pekanbaru.Keywords: Residual of food material and chef creativity